Analisis Kendala Sistem Informasi Keluarga (SIGA) dalam Pencatatan dan Pelaporan Keluarga Berencana Pasca Persalinan (KBPP) di Provinsi Jawa Timur - Afifah Andriyani; Nurul Fitriyah; Sofyan Rizalanda (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Postpartum family planning (KBPP) is an important strategy to reduce the risk of closely spaced pregnancies and contributes to lowering maternal and infant mortality rates. The coverage of KBPP, as a key performance indicator of the Bangga Kencana Program, is influenced by the quality of recording and reporting through the Family Information System (SIGA). This study aimed to analyze the barriers in recording and reporting KBPP through SIGA in East Java Province. This study used a descriptive qualitative approach with secondary data from KBPP coverage in SIGA in 2025 and primary data obtained through online coordination discussions involving representatives from districts/cities. Data were analyzed through data reduction, coding, categorization, and the development of a cause-and-effect (fishbone) diagram, and interpreted using the Human-Organization-Technology Fit (HOT-Fit) framework. The results showed that KBPP coverage was 37.29%, which remained below the national target of 57%. Most districts/cities were categorized as moderate (19) and low (16), with only 3 regions classified as high. The identified barriers included technological issues, population data discrepancies, and organizational constraints, which potentially led to underreporting. It is concluded that improving system quality, strengthening human resource capacity, and enhancing data integration are necessary to support more accurate and targeted policy-making.